2017
DOI: 10.1016/j.coisb.2017.05.019
|View full text |Cite
|
Sign up to set email alerts
|

Improvements in protein production in mammalian cells from targeted metabolic engineering

Abstract: Bioprocess optimization has yielded powerful clones for biotherapeutic production. However, new genomic technologies allow more targeted approaches to cell line development. Here we review efforts to enhance protein production in mammalian cells through metabolic engineering. Most efforts aimed to reduce toxic byproducts accumulation to enhance protein productivity. However, recent work highlights the possibility of regulating other desirable traits (e.g., apoptosis and glycosylation) by targeting central meta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
21
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
3
1

Relationship

3
5

Authors

Journals

citations
Cited by 36 publications
(21 citation statements)
references
References 61 publications
0
21
0
Order By: Relevance
“…These resources have enhanced the use of transcriptomics, proteomics, genetic engineering, and other technologies [Kildegaard et al, 2013], [Lee et al, 2015a], [Richelle and Lewis, 2017] to understand and engineer desired traits in cells. However, to improve accuracy in such endeavors, there is a need for genomic resources with far more contiguous sequence and less pervasive gaps.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These resources have enhanced the use of transcriptomics, proteomics, genetic engineering, and other technologies [Kildegaard et al, 2013], [Lee et al, 2015a], [Richelle and Lewis, 2017] to understand and engineer desired traits in cells. However, to improve accuracy in such endeavors, there is a need for genomic resources with far more contiguous sequence and less pervasive gaps.…”
Section: Introductionmentioning
confidence: 99%
“…To facilitate CHO cell research and development, the community relies on published genomes for the CHO-K1 cell line and the parent Chinese hamster, sequenced using short-read Illumina technologies (Brinkrolf et al, 2013;Lewis et al, 2013;Xu et al, 2011;Yusufi et al, 2017). These resources have enhanced the use of transcriptomics, proteomics, genetic engineering, and other technologies (Kildegaard, Baycin-Hizal, Lewis, & Betenbaugh, 2013;Lee, Grav, Lewis, & Faustrup Kildegaard, 2015;Richelle & Lewis, 2017) to understand and engineer desired traits in cells. However, to improve the accuracy in such endeavors, there is a need for genomic resources with a far more contiguous sequence and less pervasive gaps.…”
mentioning
confidence: 99%
“…Here we perform a genome-wide study of viral resistance in CHO, thereby demonstrating the utility of systems biology approaches to not only improve host cell productivity and metabolism 70-72 , but also to improve product safety. Specifically, we demonstrated that STAT1 and other key regulators contribute to the inhibition of RNA virus replication in CHO cell lines.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have focused on optimizing the production of recombinant proteins in CHO cells (35). In such studies, different omics approaches were used for understanding the reasons of higher levels of mAb production in a selected CHO cell line (68).…”
Section: Introductionmentioning
confidence: 99%